Acute effects of physical exercises on the inflammatory markers of patients with fibromyalgia syndrome: A systematic review - Sieczkowska S.M.* (2018)
© 2017 Elsevier B.V.Objective In patients with fibromyalgia (FM), exercise is indicated for symptomatic treatment. However, little is known about the inflammatory response to acute exercise in these patients. This study examines the acute effects of exercise on the inflammatory response in patients with FM. Methods A systematic review was conducted using PubMed, PsycINFO, Web of Science, SportDiscus, Scopus, Virtual Health Library (VHL), and Cochrane Library databases. Results Six studies that met the inclusion criteria were included in the analysis; three of them evaluated the effects of resistive exercise, while three evaluated the effects of aerobic exercise. Several studies evaluated pro-inflammatory (interleukin [IL]-6, IL-8, IL-1β IL-18, tumor necrosis factor-α) and anti-inflammatory cytokine levels (IL-10) and stress (Hsp72) protein levels before and after the intervention with exercise. Studies found a low-grade baseline chronic inflammatory state in patients with FM, demonstrated by the alteration of one or more of the studied markers. Conclusions We suggest that patients with FM probably have low-grade chronic inflammation, because studies found higher concentrations of IL-8 and TNF-α and high expression of IL-10 in these patients; however, the effects of exercise on the inflammatory markers in these patients are unclear. Although more research is needed on the effect of exercise on inflammation, none of the studies reported worsening of symptoms with exercise recommended as treatment.